The world beyond the West : perspectives from Eastern Europe - Kałczewiak, Mariusz, 1987- 1987- Herausgeber; Kozłowska, Magdalena, ca. 20/21 Jh. ca. 20/21 Jh. Herausgeber (New perspectives on Central and Eastern European studies;, 2022)
"No matter how one defines its extent and borders, Eastern Europe has long been understood as a liminal space, one whose undeniable cultural and historical continuities with Western Europe have been belied by its status as an "Other" in the Western imagination. Across illuminating and provocative case studies, The World beyond the West focuses on the region's ambiguous relationship to historical processes of colonialism and Orientalism. In exploring encounters with distant lands through politics, travel, migration, and exchange, it places Eastern Europe at the heart of its analysis while decentering the most familiar narratives and recasting the history of the region"